Analisis Komparatif Belanja Kesehatan dan Belanja Pendidikan Pada Masa Pandemi dan Setelah Pandemi Coronavirus Disease 2019 (Covid-19) - Arief, Ihsan; Ramli, Muhammad Ridha (Jurnal Riset AKuntansi dan Bisnis, 2024)
The purpose of this study is to examine whether there are differences in health and education expenditures in local governments across Indonesia during and after the Covid-19 pandemic.Utilizing a quantitative approach, the study includes a sample of all 508 regencies/cities in Indonesia and employs paired sample t-tests to test the hypotheses. The findings indicate that there are no significant differences in health or education expenditures during and after the Covid-19 pandemic in these regions.